2015
DOI: 10.2134/jeq2015.01.0029
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Phosphorus Loss Potential from Biosolids-Amended Soils and Biotic Response in the Receiving Water

Abstract: Application of municipal biosolids to agricultural soil can improve soil quality and improve crop yields. However, runoff or tile leachate from biosolids-applied fields may contribute to localized eutrophication of surface water. A laboratory experiment was conducted to determine loss potential of nutrients from soils amended with two different biosolids (anaerobically digested and chemically stabilized) relative to loss from a reference soil and to determine response in freshwater microcosms to nutrients lost… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although not included in this model’s scope, it is important to note that biosolids and artificial fertilizers could have different impacts after application. For example, nutrient runoff might be higher from artificial fertilizer, and biosolids land application can imply the risk of contaminating soil and adjacent waterways with heavy metals and persistent organic micropollutants. …”
Section: Resultsmentioning
confidence: 99%
“…Although not included in this model’s scope, it is important to note that biosolids and artificial fertilizers could have different impacts after application. For example, nutrient runoff might be higher from artificial fertilizer, and biosolids land application can imply the risk of contaminating soil and adjacent waterways with heavy metals and persistent organic micropollutants. …”
Section: Resultsmentioning
confidence: 99%
“…Within the five months of the research, leachate from both biosolids-amended soil columns and reference soil columns demonstrated phosphorus concentrations around 0.039-0.054 mg/L. These concentrations were much smaller than the concentrations of phosphorus measured in runoff from biosolids-amended soils [17,20,29,[36][37][38]. but still exceeded concentrations suggested as optimal for limiting eutrophication potential (below 0.025 mg/L in streams and 0.01 mg/L in lakes) [39].…”
Section: Resultsmentioning
confidence: 79%
“…Runoff and erosion are important pathways of soil phosphorus loss [9,10], and the majority of studies on phosphorus loss from agricultural land are devoted to losses through runoff and erosion [11][12][13][14][15][16]. Application of municipal biosolids, specifically, can increase total phosphorus (TP) in runoff from soil in laboratory mesocosms [17], although loss of P in runoff in agricultural soils may be dependent on the stabilization method used to produce the biosolids [18][19][20]. These losses represent only horizontal migration of phosphorus through surface runoff, while vertical migration of phosphorus through the soil layers can also contribute to the phosphorus escape from agricultural lands [21].…”
Section: Introductionmentioning
confidence: 99%